Advanced and innovative strategies for high efficiency: organic and inorganic solar cells - Ikram ANEFNAF (Faculté des Sciences de Rabat, 2021)
The main work of this thesis is divided into two parts: The first has an objective to shed light on the feasibility of developing a novel wide band-gap kesterite based solar cells using pure Ge (Cu2ZnGeSe4), as an alternative solution to overcome the drawbacks related to free Ge-kesterite solar cells (Tin-kesterite). To fulfill this general objective, the following sub-objectives are proposed and experimented: (i) optimization of sequential processes for Cu2ZnGeSe4 absorbers synthesis, (ii) study and identification of defect types and concentrations of off-stoichiometric concentrations of CZGeSe and (iii) understanding the main losses mechanisms limiting the performance of kesterite CZGeSe. In the second part, the elaboration and characterization of efficient inverted bulk heterojunction organic devices are presented and discussed. The second part of this thesis is dedicated to optimize and analyze organic solar cells using different organic materials, small molecules (fullerene derivatives) as acceptors and conjugated polymers as donors.
Stratégies avancées et innovantes pour les cellules solaires organiques et inorganiques à haut rendement
Keywords: Chimie; Chimie